Dublin's fourth office development boom - MacLaran, Andrew; O'Connell, Roland (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2003)
The past seven years have comprised a period of considerable activity in the office development sector in Dublin. Between January 1999 and December 2003, over 856,000 sq. m. of office space was completed. creating a 50 per cent increase in the size of the modem (post-1960) office stock. This article reviews the associated trends in the scale of development, take-up and vacancy over the past decade. The data are drawn from the Hamilton Osborne King/Trinity College Dublin database and annual office reviews compiled annually since 1989. An examination of the two earlier development booms is provided by MacLaran, MacLaran and Malone (1987), with a review of the third development boom being included in MacLaran (1993) and Drudy and MacLaran (1994).
Papers from practice
Keywords: Urban geography -- Ireland